2018
DOI: 10.1002/chem.201802958
|View full text |Cite
|
Sign up to set email alerts
|

Neutral, Cationic and Hydride‐substituted Siloxygermylenes

Abstract: The introduction of the labile trimethylsiloxy group to Ge centers in the presence of an N-heterocyclic carbene donor is reported. The new complex IPr⋅GeCl(OSiMe ) (IPr=[(HCNDipp) C:]; Dipp=2,6-iPr C H ) was readily converted into the structurally unique Ge siloxy(hydrido)germylene IPr⋅GeH(OSiMe )⋅BH by treatment with lithium borohydride. Additionally, the reactive siloxygermylene cation [IPr⋅Ge(OSiMe )] was synthesized and clean oxidative addition of CH Cl was demonstrated. The two-coordinate [IPr⋅Ge(OSiMe )]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 103 publications
6
34
0
Order By: Relevance
“…In these reactions, heteroatom reagents are thought to act as Lewis acids. Transformations of M–NHC to B–NHC bonds have been reported for Li/NHC, 108 Fe II /NHC 137 and Ge II /NHC 122 complexes ( Table 1 column 4). For example, reaction between Ge II /NHC complex 40 and LiBH 4 in Et 2 O affords NHC–BH 3 adduct 41 ( Scheme 9 ).…”
Section: Organometallic Chemistry Behind the H–nhc C–nhc And X–nhc Cmentioning
confidence: 79%
See 1 more Smart Citation
“…In these reactions, heteroatom reagents are thought to act as Lewis acids. Transformations of M–NHC to B–NHC bonds have been reported for Li/NHC, 108 Fe II /NHC 137 and Ge II /NHC 122 complexes ( Table 1 column 4). For example, reaction between Ge II /NHC complex 40 and LiBH 4 in Et 2 O affords NHC–BH 3 adduct 41 ( Scheme 9 ).…”
Section: Organometallic Chemistry Behind the H–nhc C–nhc And X–nhc Cmentioning
confidence: 79%
“…For example, reaction between Ge II /NHC complex 40 and LiBH 4 in Et 2 O affords NHC–BH 3 adduct 41 ( Scheme 9 ). 122 Reaction of complex 42 with Me 3 SiCl affords compound 43 ( Scheme 9 ). 108 A similar adduct was detected by NMR in a C 6 D 6 solution of [Pd(I t Bu) 2 ] complex and Me 3 SiI after 40 day storage at room temperature; 175 the authors suggested that the NHC–SiMe 3 adduct was formed via Pd–NHC dissociation and subsequent reaction of the free NHC with Me 3 SiI.…”
Section: Organometallic Chemistry Behind the H–nhc C–nhc And X–nhc Cmentioning
confidence: 99%
“…The first example of Ge(II) cation catalyzed hydroboration was reported by Rivard and coworkers. [77] They have synthesized a siloxygermylene cation [IPr•Ge(OSiMe 3 )][BAr 4 F ] (33) (Scheme 31) and utilized it for the hydroboration of sterically crowded benzophenone and electron-rich pinacolone. The conversion was done under mild conditions with quantitative yields.…”
Section: Hydroboration By Re(ii)x (E = Ge Sn; X = Otf Bar F Gacl mentioning
confidence: 99%
“…In contrast to hydroboration, the hydrosilylation of carbonyl compounds has been explored more . There are reports of a wide variety of metal catalysts from main group elements, including catalysts based on alkali or alkaline earth metals, namely, Al, Si, Ge, Sn, as well as rare earth metal catalysts such as those based on La and Yb, which have been used in the hydroboration of carbonyl compounds (Figure ). Transition metals such as Ti, Mn, Fe, Mo, Rh, Ru, Co, and Cu have also been used as the bases for developing catalysts.…”
Section: Introductionmentioning
confidence: 99%